Relationship between career decision-making and perceived parental career behaviours among students of a private higher educational institution in Malaysia - Wong, Kah Yee; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
One of the distinctive features of career counselling research was the study of the individual’s career decision-making. Many career development theories are established and enrooted from West, which its society culture rooted with individualistic; and previous researchers highlighted personal aptitudes, personalities, and values, which lack of cultural sensitivity. The purpose of this study aimed to examine the relationship between career decision-making and perceived parental career behaviours amongst students of a private higher educational institute in Malaysia. In this study, Career Decision Self-Efficacy Scale-Short Form (CDSE-SF) and Parent Career Behaviour Checklist were utilized. Finally, the null hypothesis of relationship between perceived parental career behaviours and career decision-making was rejected.